Investigation and evaluation of cadmium in crabs sold in Beijing from 2018 to 2020 - XING Shige; Liu Tong; LI Yongliang; YAO Guihong; ZHANG Yujia; WANG Haiyue; ZHANG Feng (Zhongguo shipin weisheng zazhi, 2021)
ObjectiveTo detect the content of Cadmium (Cd) in crab sold in Beijing from 2018 to 2020 and carry out health risk assessment.MethodsRandom sampling method was adopted, common crab sold in Beijing were sampled. The content of Cd was determined by atomic absorption spectroscopy to evaluate the health risk.ResultsA total of 83 crab samples were collected. The average level of Cd in crabs was 0.647 mg/kg. Among them, the Cd content in freshwater crabs ranged from 0.043-0.620 mg/kg with the average level of 0.183 mg/kg. Whereas, the concentration of Cd in seawater crabs ranged from 0.033-3.200 mg/kg with the average level of 1.070 mg/kg. Moreover, the difference of the over-limit ratio was significant during three year. The THQ value and total THQ value of heavy metals in crab ingested by children and adults decreased in turn. The THQ values of Cd were less than 1.ConclusionAlthough the results indicated that there were certain amounts of Cd residues in the crabs sold in Beijing during 2018-2020, the dietary risk was relatively low because of the low intake.